2018
DOI: 10.3390/atmos9110424
|View full text |Cite
|
Sign up to set email alerts
|

Ambient PM2.5 Human Health Effects—Findings in China and Research Directions

Abstract: Exposure to fine particulate matter (PM) results in adverse health outcomes. Although this is a global concern, residents of China may be particularly vulnerable due to frequent severe air pollution episodes associated with economic growth, industrialization, and urbanization. Until 2012, PM2.5 was not regulated and monitored in China and annual average concentrations far exceeded the World Health Organizations guidelines of 10 μg/m3. Since the establishment of PM2.5 Ambient Air Quality Criteria in 2012, conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(39 citation statements)
references
References 84 publications
3
32
0
1
Order By: Relevance
“…High amounts of ne particulate matter in indoor and outdoor environs noted in the study were similar to those found in highly petroleum-based industrial areas [23][24][25][26][27][62][63][64]. The observed increase in particulate matter is most likely responsible for the relative upsurge in trends of morbidity and mortality recorded over the years in Port Harcourt, con rming reports from previous studies [19,20,62], as toxicity and mortality, cancers, upsurge in respiratory, cardiovascular, and renal dysfunctions resulting from exposure to particulate matter bonded with PAHs have been reported in a plethora of epidemiological studies [47,65,44]. Although the ration of PM 10 and PM 2.5 have not been studied for atmospheric particulate matter of Port Harcourt, studies have implicated infants and children being at risk of ne aerodynamic particulates [22,66].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…High amounts of ne particulate matter in indoor and outdoor environs noted in the study were similar to those found in highly petroleum-based industrial areas [23][24][25][26][27][62][63][64]. The observed increase in particulate matter is most likely responsible for the relative upsurge in trends of morbidity and mortality recorded over the years in Port Harcourt, con rming reports from previous studies [19,20,62], as toxicity and mortality, cancers, upsurge in respiratory, cardiovascular, and renal dysfunctions resulting from exposure to particulate matter bonded with PAHs have been reported in a plethora of epidemiological studies [47,65,44]. Although the ration of PM 10 and PM 2.5 have not been studied for atmospheric particulate matter of Port Harcourt, studies have implicated infants and children being at risk of ne aerodynamic particulates [22,66].…”
Section: Discussionsupporting
confidence: 81%
“…3 and 4) implicating a relatively clean air in the University of Nigeria Nsukka, where the experimental animals were imported from for the study assessment. This suggests that people in non-hydrocarbon and petroleum-free environments are at lower risk of cancers and general tissue toxicity compared to residents inhaling air polluted with PAHs bonded particulate matter due to petroleum and hydrocarbon related industrial activities [61][62][63][64][65][66][67]. Also, the continuous inhalation of PAHs bounded particulate increases the concentrations of these compounds in the tissues, enabling toxicity through oxidative stress, in ammation, and DNA methylation [5,48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The adverse effects of PM 2.5 on the respiratory-cardiovascular system have been repeatedly confirmed [1][2][3][4][5][6][7][8][9][10][11][12]. Epidemiologic studies that assess exposure risk to different ambient PM 2.5 concentration levels have relied on the U.S. Environmental Protection Agency's (EPA) network of ground-based ambient air pollutant monitors [4,[13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown a link between pollutants (polycyclic aromatic hydrocarbons) and maternal thyroid function [1]. Particulate air pollutants are prevalent and harmful to humans (as assessed versus mortality, morbidity or cardiovascular disease) [2]; however, data on whether exposure to particulate air pollutants can also disrupt thyroid function in pregnancy are limited. Recently, exposure to ambient air pollution (and more in detail to nitrogen dioxide-NO 2 or particulate air pollutants with a diameter of less than 2.5 micrometers-PM2.5 or 10 micrometers-PM10) has been linked to thyroid (dys)function in pregnant women (and/or their fetuses/neonates) [1,[3][4][5].…”
Section: Introductionmentioning
confidence: 99%